Biological Activities of Oryzanol, Stigmasterol and Microminutinin on Human Breast Cancer Cell-Line, Mcf7 - Md Akim, Abdah (2004)
Researchers are exploring better treatments in cancer. The identification of active plant chemicals and the study of their biological activities are extensively being pursued. The five objectives in this study were to determine the antioxidant activity of rice bran extracts, to isolate oryzanol from rice bran, to determine the cytotoxicity activity of oryzanol, stigmasterol and microminutinin, to investigate the morphological changes in MCF7 cells treated with oryzanol, stigmasterol and microminutinin and to study on the effect of these compounds on c-myc, c-fos and c-erbB2 gene expression. The antioxidant activities of various rice bran extracts were carried out to determine the best organic solvent extraction. In the Ferric Thiocyanate (FTC) and Thiobarbiturate (TBA) assays, chloroform extract (FTC; 92%, TBA; 82%) had the highest antioxidant activity followed by ethyl acetate (FTC;90%, TBA;79%) methanol (FTC;90%, TBA;79%) and hexane (FTC; 89%, TBA;77%) extracts. The antioxidant activities in the ~-carotene degradation assay gave similar findings. Comparison between the antioxidant activities